The effect of systematic and unsystematic determinants on loan (financing) to deposit ratio in Indonesian banking - Mohammad Iqbal Irfany; Muhammad Fikra Yafi Ulhaqqi (goodwood publishing, 2023)
Purpose: This study compares the determinants of liquidity of Islamic Banks (IBs) and Conventional Banks (CBs) based on the loan-to-deposit ratio (LDR) and financing-to-deposit ratio (FDR) between 2016 and 2020. Research Methodology: The data analysis technique used was panel data regression. Results: The results show Economic growth has a positive effect on banking liquidity risk, while non-performing loans (financing) have a negative effect on banking liquidity risk. Limitations: The frame time in this research was 2016-2020 which, before Bank Syariah Mandiri, Bank Rakyat Indonesia (BRI) Syariah, and Bank Negara Indonesia (BNI) Syariah merged into Bank Syariah Indonesia. Contribution: This study can be used as a reference for preparing or perfecting regulations that can be bolder in expanding credit (financing). Commercial banks are expected to be able to manage liquidity so that the liquidity ratio is not less than or exceeds the tolerance limit, especially for CBs, and are used as evaluation material for the performance of IBs, especially CBs. Novelty: Several previous studies conducted separate analyses of the determinants of LDR and FDR in one type of commercial bank and showed contradictory results. This research did not conduct separate analyses in one type of bank but combined the determinants so that they could cause liquidity risk by measuring LDR on BUK and FDR on BUS to discuss these conflicting findings.